GINGGER INSUFED WATER TO INCREASED PEAK FLOW RATE ON SMOKERS - Rian Yuliyana; Elsa Gusrianti; Yunita Yunita (International Journal of Social Science, 2021)
The increase in consumers of cigarettes will have an impact on the higher burden of disease and the increase in the mortality rate of smokers in the world. Ginger has many health benefits and is used as an ingredient for healing respiratory tract diseases. Ginger Infused water is a type of drink containing drinking water and fruits with immersion in a certain time which is currently rife among the public. to determine the effect of giving Gingger Infusion of Water to Peak Expiratoy Flow Rate in Active Smokers in Tanjungpinang. This type of research was a quasi-experimental approach with a pretest and posttest approach with a control group design. The population of this study was 115 active smokers, the sample of this study was 40 respondents who were divided into 20 intervention groups and 20 control groups. The sampling technique used was accidental sampling. In this ginger infusion water study, there was a significant difference in peak flow rate scores before and after being given ginger water infusion in the intervention group and without ginger water infusion/warm water in the control group (p<0.05). It is expected that smokers can drink ginger infusion water continuously to maintain lung expansion